2022
DOI: 10.1039/d1ew00774b
|View full text |Cite
|
Sign up to set email alerts
|

Photo-chemical/catalytic oxidative/reductive decomposition of per- and poly-fluoroalkyl substances (PFAS), decomposition mechanisms and effects of key factors: a review

Abstract: Per- and poly-fluoroalkyl substances (PFAS) are a group of diverse anthropogenic chemicals with a wide range of industrial and commercial applications. Worldwide detection of legacy and emerging PFAS, as well...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 197 publications
(444 reference statements)
0
25
0
Order By: Relevance
“…For decades, per- and polyfluoroalkyl substances (PFAS) chemicals have been widely used in various consumer, medical, and industrial products. Owing to environmental persistence and being notoriously hazardous, the long-chain PFAS chemicalsperfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS)have been prohibited under international regulations. , However, many short-chain fluorinated alternatives remain in use, and they could also be accumulated via physicochemical degradation pathways of longer-chain PFAS. Even though the use of hydrated electron (e aq – )-based advanced reductive technology (e aq – -ART) has recently shown to be effective to destruct both perfluoroalkyl carboxylates (PFxA, x = number of carbons comprising the hydrophobic tail) and perfluoroalkyl sulfonates (PFxS), PFxS with short fluoroalkyl chains such as PFBS (C 4 F 9 SO 3 – ) remains an exceptional case and displays very sluggish reactivity . To date, the abundance of short-chain PFAS from numerous sources has already been detected in most locations on the planet. Recent toxicological studies revealed that the potential threats to human health posed by analogs had been underestimated due to increased solubility, mobility, and inertness. Thus, their complete removal and decomposition from the aquatic environment has become an urgent concern.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, per- and polyfluoroalkyl substances (PFAS) chemicals have been widely used in various consumer, medical, and industrial products. Owing to environmental persistence and being notoriously hazardous, the long-chain PFAS chemicalsperfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS)have been prohibited under international regulations. , However, many short-chain fluorinated alternatives remain in use, and they could also be accumulated via physicochemical degradation pathways of longer-chain PFAS. Even though the use of hydrated electron (e aq – )-based advanced reductive technology (e aq – -ART) has recently shown to be effective to destruct both perfluoroalkyl carboxylates (PFxA, x = number of carbons comprising the hydrophobic tail) and perfluoroalkyl sulfonates (PFxS), PFxS with short fluoroalkyl chains such as PFBS (C 4 F 9 SO 3 – ) remains an exceptional case and displays very sluggish reactivity . To date, the abundance of short-chain PFAS from numerous sources has already been detected in most locations on the planet. Recent toxicological studies revealed that the potential threats to human health posed by analogs had been underestimated due to increased solubility, mobility, and inertness. Thus, their complete removal and decomposition from the aquatic environment has become an urgent concern.…”
Section: Introductionmentioning
confidence: 99%
“…These data demonstrate that the different exposure wavelengths do not produce significantly different TPs. Photodegradation of PFASs can occur, although at a low extent, and the reactions are dependent on irradiation wavelength and intensity, PFAS concentration and structure, and exposure duration . Thus, we expected to see different TPs between the two wavelengths and potentially more TPs in the 193 nm exposures due to the greater photon energy of 193 nm photons, which can induce greater PFAS degradation .…”
Section: Resultsmentioning
confidence: 99%
“…30 However, previous studies noted the importance of long irradiation times (>12 h) to achieve even negligible photolysis of PFASs. 30 Therefore, we conclude that the exposure durations used in these experiments, which mimic those of fabs, are not sufficient to induce significant photodegradation of PFASs at either 248 or 193 nm (Figure 3).…”
Section: Pfas Standards and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations